Efficiency of AX.25 Protocol in a Wireless SCADA Communication System for Monitoring Performance of Micro-Hydro Power Plants. Issue 1 (June 2019) - Salahuddin,; Bakhtiar,; Yusman,; Fadhli,
Abstract: This paper presents the results of testing and estimating the efficiency of the AX.25 protocol implemented in the wireless SCADA communication system for monitoring the performance of the Micro-hydro Power Plant (MHPP). This protocol is commonly used for packet radio communications. AX.25 is a layer 2 protocol (referring to the OSI layer reference), the Data Link Layer. As a layer 2 protocol, AX.25 is responsible for building link connections, providing logic procedures for transferring connections and disconnection. This system can monitor several MHPP parameters such as voltage, current, frequency, and turbine rotation and can be accessed directly at one centralized location. Data from sensors installed in the generator are converted into digital data on the microcontroller contained in the Remote Terminal Unit (RTU). This data is then sent to the Main Terminal unit (MTU) so that it can be a reference for operators to decide further if there are MHPP parameters that change from the predetermined standard. AX.25 protocol is implemented on an arduino microcontroller hardware that functions as a Terminal Node Controller (TNC) that will regulate the traffic of data communication between several RTUs and MTU. In accordance with RTU requests, TNC will forward the data sent by the RTU with certain "call signs" to be forwarded to MTU and displayed at the monitoring center. The test results show that the efficiency of AX.25 protocol at transmission rates of 1.2 kbps, 2.4 kbps, 4.8 kbps and 9.6 kbps tends to be linear with respect to changes in delivery start-up time and does not have a significant impact on changes in start-up time transmitter. For all given k values, when T103 = 5, regardless of transmission rate, the protocol can achieve an efficiency of around 90%.